Some Analyses on an Artisan Census in the Early 20th Century - Turna, Nalan (HACETTEPE UNIV, 2020)
The Ottoman State took artisan censuses for various reasons, such as taxation and security. Aiming to contribute to the existing literature that has studied the Ottoman artisans and occupational groups in various ways, the present article examines an artisan census from the first quarter of the 20th century. This census, probably taken during the reign of Sultan Abdulhamid II to prevent making guns and bombs for rebellious Armenians, comprised of 1020 people and 48 occupations (a few factory owners and factory workers included). With this census, it would be possible to explore ordinary people, including artisans and workers. The article first mentions the literature on the relevant subject and then gives background information to the Ottoman artisan censuses. After situating the subject into its historical context, it details the said artisan census that gives the name of the artisan, his father's name, the name of his profession, his position, and his workplace and residence addresses. The article evaluates the shop locations where artisans worked, the artisans' combinations (masters, journeyman, apprentice) in the same place, and the factory workers. It also analyses workplace-residence relation, artisans who stayed overnight either at their workplaces or houses, rooms, casinos, coffeehouses, etc. and finally, the blacksmith, the biggest artisanal group in the list. Thus, this article, examining an artisan census from the early 20th century, contributes to the studies on Ottoman artisans and occupational groups
Keywords: Istanbul; Artisan; Census; Armenians; the reign of Sultan Abdulhamid II; History